THE CONSTITUTIONAL COURT OF CROATIA AND THE CONCEPT OF INHERENT POWERS - Gardašević, Đorđe; Jarak, Niko (Pravni zapisi, 2025)
The article examines the Croatian Constitutional Court’s interpretive approach to the existence of its own “inherent” powers and their relationship to the powers enumerated in the Constitution. In this context, we analyze the relevant case law of the Constitutional Court through several key questions: does the Court exercise its “inherent” powers through the concept of a descriptive or autonomous norm, does this result in significant changes in the Court’s procedures, does the Court apply measures defined by the Constitution, and does this significantly disrupt the constitutional balance of competences and powers. The findings show that the Court applies the concept of the autonomous norm, thereby significantly altering both its procedures and the measures it is authorized to impose. We conclude that such an approach by the Court significantly undermines the principle of the balance of powers as envisaged in the Constitution.
Keywords: Constitutional Court of the Republic of Croatia; Constitutional Adjudication; Constitutional Interpretation; Inherent Powers; Enumerated Powers,; Separation of Powers